Hereditary vitamin D-resistant rickets: a report of four cases with two novel variants in the VDR gene and successful use of intermittent intravenous calcium via a peripheral route - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WALTER DE GRUYTER GMBH, 2020)
Background: Hereditary vitamin D-resistant rickets (HVDRR) is caused by vitamin D receptor (VDR) defects. Patients with HVDRR do not respond to standard doses of calcitriol and oral calcium (Ca) treatment and need to be treated with intravenous Ca (IV-Ca) via a central route. However, central catheter-related complications can cause significant morbidity. Case presentation: Four unrelated patients with HVDRR presenting with rickets and alopecia totalis were administered intermittent IV-Ca treatment (2-5 times/week) through a peripheral route. No complications such as infection, extravasation or arrhythmias were detected upon peripheral infusion. Peripheral 1-22 months'-duration of IV-Ca normalized parathyroid hormone (PTH) and alkaline phosphatase (ALP) in all patients, after which, oral Ca of 200-400 mg/kg/day and calcitriol of 0.5 mu g/kg/day were sufficient to maintain normal PTH levels. Molecular studies on the VDR gene showed a previously reported homozygous c.454C > T (p.Q152*) pathogenic variant in two patients. Two novel homozygous variants in the other two patients were detected: (1) c.756-2A > G, which affects the splice acceptor site, and (2) c.66dupG (p.I23Dfs*20) variant leading to a frameshift that results in a premature stop codon. Conclusions: Peripheral IV-Ca treatment is an effective and practical alternative treatment mode that provides dramatic clinical benefit in patients with HVDRR.
Keywords: calcium; hereditary vitamin D-resistant rickets; VDR gene; vitamin D receptor; D-DEPENDENT RICKETS; BINDING DOMAIN; MUTATION; HORMONE; SERVER